2010
DOI: 10.1002/ijc.25632
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic function of charged multivesicular body protein 5: A potentially relevant gene in acute myeloid leukemia

Abstract: In recent years, RNA interference (RNAi) has been widely used to uncover gene function or pathway context of novel genes. In our study, we describe a short-hairpin RNA-based RNAi screening of a set of functionally uncharacterized human genes for their possible capability to inhibit apoptosis. We thereby identified a new antiapoptotic function for CHMP5 (charged multivesicular body protein 5), which was confirmed by overexpression and rescue assays. Furthermore, caspase assays showed that CHMP5 silencing induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
5
12
0
Order By: Relevance
“…Moreover, our studies are consistent with previous studies which show that CHMP5 is an anti-apoptotic gene [8,9] . Furthermore, in agreement with these previous studies, we found that the CHMP5 gene expression is significantly increased in de novo or relapsed AML, indicating that it may participate in leukemogenesis [8,9] .…”
Section: Chmp5 Gene and Protein Changes After Scfv Retrovirus Infectionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, our studies are consistent with previous studies which show that CHMP5 is an anti-apoptotic gene [8,9] . Furthermore, in agreement with these previous studies, we found that the CHMP5 gene expression is significantly increased in de novo or relapsed AML, indicating that it may participate in leukemogenesis [8,9] .…”
Section: Chmp5 Gene and Protein Changes After Scfv Retrovirus Infectionsupporting
confidence: 93%
“…Moreover, our studies are consistent with previous studies which show that CHMP5 is an anti-apoptotic gene [8,9] . Furthermore, in agreement with these previous studies, we found that the CHMP5 gene expression is significantly increased in de novo or relapsed AML, indicating that it may participate in leukemogenesis [8,9] . As shown in Figure 1, after CHMP5 is inhibited by RNA interference in the AML leukemic cell line, U937, the expression of the CHMP5 protein is significantly decreased, and the leukemic cells are induced to undergo apoptosis [8] .…”
Section: Chmp5 Gene and Protein Changes After Scfv Retrovirus Infectionsupporting
confidence: 93%
See 2 more Smart Citations
“…Functional analyses of CHMP5 have been carried out in our lab using RNAi and protein overexpression strategies. We found that CHMP5 is an anti-apoptotic gene [11], consistent with the findings of Shahmoradgoli et al [12]. Moreover, we also found that CHMP5 was significantly increased in de novo or relapsed acute leukemia, indicating that it may participate in leukemogenesis [11,12].…”
Section: Introductionsupporting
confidence: 81%